The Effectiveness of Group Discussion Method in Promoting Student’s Reading Comprehension - Rusli, Sucitra; Pakaja, Marina; Habibie, Alvons (English Education Department, 2024)
The objective of the study is to find out whether Teaching reading comprehension through the group discussion method isefficacious in improving students' reading ability and to know how significant the effect of the group discussion method is on the students' reading comprehension in the 3rd semester of the English Education Department. The population in this study were all 3rd-semester students majoring in English education, with a total of 26 people. The data collection method is based on pre-tests and post-tests. research data were then analyzed using the t-test to see the increase in students' reading comprehension. the results of the study showed that the average pre-test and post-test increased. This can answer theresearch question, namely, whether the group discussion method is effective enough in improving students' reading comprehension of narrative texts, as evidenced by the average post-test score in the control class of 69.2. In the experimental class, it has an average value of 73.0. The result of this study indicated that the group discussion method was effective. From this study, the researcher concluded that the Group Discussion method (cooperative learning) is effective in learning reading comprehension of narrative text.